Clinical characteristics of primary atrial tumor and their diagnostic value: A retrospective study of 10 years - Wang, Qian; Jiang, Yue; Lin, Li; Li, Sheng; Lv, Jiagao; Chen, Jun (Frontiers in Surgery, 2023)
Background: Primary atrial tumors are relatively rare and predominantly benign. However, some atrial tumors may be malignant and are associated with poor outcome. Currently, it is hard to determine the malignance of atrial tumors by preoperative clinical presentation or by echocardiography. We aimed to report the difference in the clinical characteristics of patients with benign and malignant atrial tumor. Methods: This was a single-center retrospective study. A total of 194 patients with primary atrial tumor admitted to our center between 2012 and 2021 were included. The clinical characteristics of patients with benign and malignant tumor were compared. Results: Benign and malignant tumor accounted for 93% (n=180) and 7% (n=14) of the total patients, respectively. Malignant atrial tumor tended to occur in younger patients (P < 0.05), was more likely to be located at the right atrium (P < 0.05), and tended to attach to the atrial wall or valve instead of the atrial septum. Fever symptoms were more common in patients with malignant tumors than in patients with benign tumors (P<0.05). Compared to benign tumor, patients with malignant atrial tumor also demonstrated higher rates of fever, lower rates of increasing fibrinogen, increased blood glucose (P<0.05), significantly longer prothrombin time, and lower prothrombin activity (P<0.05). Patients with malignant primary atrial tumor had higher mortality rate, tumor metastasis rate, and tumor recurrence rate than patients with benign primary atrial tumor (P<0.05). Conclusion: We compared the clinical characteristics of patients with benign and malignant atrial tumor. These findings provide valuable information to preoperatively determine the malignance of atrial tumor and thus guide surgical treatment.